Youth activism through Social media in Assam: An Exploratory Study - MANOJ DEORI; SUNIL K. BEHERA (Dr. Chinmay Pandya, 2014)
The paper is an attempt to study the online participation behavior of youth in Assam in organizing social and political protests through Social media. During several protest demonstrations and rallies which took place in the middle of the year, 2012; there has been a series of cyber activism that took place prior to the street demonstrations and rallies. The paper attempts to justify the fact that, the street demonstrations and rallies which took place during that particular period, gained its momentum largely through Social Media. Therefore the period can be regarded as the beginning of cyber activism in Assam, since such online activities in publicizing and organizing any collective action in the physical world with regards to activism was not seen in the past. Based on the data collected through onsite surveys, such online communities have considerably given rise to new forms of collective action such as on/offline social and political protest in Assam through social media by publicizing and organizing people where the predominance of the youths is distinctly visible. It is seen that, there has been an increasing number of cyber activism among the online 'Assamese' youth communities which has apparently given raise to cyber-civil societies in urban areas. The predominance of youth in such protests is visible, since the use of social media has become a popular culture among the youth.  About 17% of the Indian populations are between 15 and 24 and they are experiencing the changes brought by the New Media technology. In examining the practices on social media, authors focus primarily on "Facebook", which is the most popular social networking site in social media. Series of protest took place in the months of July, August and September, 2012 against unethical media practices; particularly the television media in Assam. Eventually protests against the insecurity of the women in Guwahati, the capital city of Assam and protest against illegal Bangladeshi immigrants in Assam were also demonstrated on the streets of Assam which gathered huge civic support. Few youth groups from Assam were also established who organized themselves through social networking sites to raise street demonstrations, along with certain other political parties, NGOs and offline civil society groups. The paper mainly studies the participation of youth in such protests and reflects on the case studies which can be regarded as the beginning of youth cyber activism that apparently gained momentum through social media in Assam.